PENERAPAN LAYANAN KONSELING INDIVIDUAL UNTUK MENGURANGI PERILAKU BULLYING KELAS VII DI SMP NEGERI 1 SIUNGGAM JULU PADANG BOLAK TENGGARA TAHUN AJARAN 2022-2023 - Rafika Sari Harahap; Sri Ngayomi Yudha Wastuti (Cahaya Ilmu Bangsa Institute, 2024)
The problem in this research is how individual counseling services reduce bullying behavior at SMP Negeri 1 Siunggam Julu Padang Bolak Tenggara 2022-2023. The aim of this research is to reduce bullying behavior in students with individual counseling services. The subjects in this research were guidance and counseling teachers, subject teachers and students of SMP Negeri 1 Siunggam Julu Padang Bolak Tenggara. The objects of this research were 3 students who behaved in bullying ways. This research instrument uses interviews and observation. This research is qualitative research using data collection methods through observation, interviews and documentation. Based on the results of the research analysis, it is known that individual services for students who bully can be reduced, thus individual counseling can reduce bullying behavior at SMP Negeri 1 Siunggam Julu Padang Bolak Tenggara 2022-2023.